Adhesive Functions or Pseudogenization of Type Va Autotransporters in Brucella Species - Bialer, Magalí G.; Ferrero, Mariana C.; Delpino, M. Victoria; Ruiz-Ranwez, Verónica; Posadas, Diana M.; Baldi, Pablo C.; Zorreguieta, Angeles (Frontiers in Cellular and Infection Microbiology, 2021)
Adhesion to host cells is a key step for successful infection of many bacterial pathogens and may define tropism to different host tissues. To do so, bacteria display adhesins on their surfaces. Brucella is an intracellular pathogen capable of proliferating in a wide variety of cell types. It has been described that BmaC, a large protein that belongs to the classical (type Va) autotransporter family, is required for efficient adhesion of Brucella suis strain 1330 to epithelial cells and fibronectin. Here we show that B. suis 1330 harbors two other type Va autotransporters (BmaA and BmaB), which, although much smaller, share significant sequence similarities with BmaC and contain the essential domains to mediate proper protein translocation to the bacterial surface. Gain and loss of function studies indicated that BmaA, BmaB, and BmaC contribute, to a greater or lesser degree, to adhesion of B. suis 1330 to different cells such as synovial fibroblasts, osteoblasts, trophoblasts, and polarized epithelial cells as well as to extracellular matrix components. It was previously shown that BmaC localizes to a single bacterial pole. Interestingly, we observed here that, similar to BmaC, the BmaB adhesin is localized mostly at a single cell pole, reinforcing the hypothesis that Brucella displays an adhesive pole. Although Brucella species have strikingly similar genomes, they clearly differ in their host preferences. Mainly, the differences identified between species appear to be at loci encoding surface proteins. A careful in silico analysis of the putative type Va autotransporter orthologues from several Brucella strains showed that the bmaB locus from Brucella abortus and both, the bmaA and bmaC loci from Brucella melitensis are pseudogenes in all strains analyzed. Results reported here evidence that all three autotransporters play a role in the adhesion properties of B. suis 1330. However, Brucella spp. exhibit extensive variations in the repertoire of functional adhesins of the classical autotransporter family that can be displayed on the bacterial surface, making them an interesting target for future studies on host preference and tropism.